O066 The Impact of Work Break Characteristics on Sleep Duration in Heavy Vehicle Drivers. (9th November 2022) - Harris, R; Beatty, C; Cori, J; Spitz, G; Soleimanloo, S; Peterson, S; Naqvi, A; Barnes, M; Downey, L; Shiferaw, B; Anderson, C; Tucker, A; et al.
Abstract: Introduction: Heavy vehicle drivers (HVDs) frequently experience reduced sleep due to travelling long distances under non-standard work hours. Short sleep in HVDs can increase risk of motor vehicle crashes and falling asleep while driving. This study sought to examine the influence of break duration between shifts, break onset time, and prior shift duration on HVDs' total sleep time (TST) between consecutive work shifts, and the interaction between break duration and break onset time. Methods: Twenty-seven HVDs' sleep and shift work were monitored for up to nine weeks through actigraphy, sleep diaries, and work diaries. Differences in TST between consecutive shifts and days off were assessed. Linear mixed models and pairwise comparisons evaluated the impact of break duration, break onset time, and prior shift duration on TST between shifts. Results: TST was significantly lower between consecutive shifts (M=6.38-hours) compared to days off (M=7.63-hours), p<.001. Longer break durations were associated with more TST, p<.001. Break durations up to 7-, 9-, and 11-hours resulted in, on average, 4.76-, 5.66-, and 6.41-hours of sleep, respectively. Breaks starting between 00:01-08:00h led to shorter TST compared to breaks starting between 16:01-20:00h, p<.05. Prior shift duration and the interaction between break duration and break onset time were not associated with TST. Discussion: HVDs' TST between workdays are independently impacted by break duration and break onset time. Break durations between 7-11-hours, reflecting Australian and European break guidelines, result in insufficient sleep. Work regulations must evaluate appropriate break durations and break onset times to allow adequate sleep in HVDs.